PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI, UMKM, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN BARITO TIMUR - Desak Putu Butsi Triyanti (Jurnal PubBis, 2019)
The purpose of this study was to find out and analyze the influence of: 1) Transformational leadership style on the performance of employees at the Office of Cooperatives, MSMEs, Industry and Trade in East Barito Regency; 2) Factors that hinder in improving the performance of employees in the Office of Cooperatives, MSMEs, Industry and Trade in East Barito Regency. This research is a quantitative study, the sample technique used is purposive sampling or purposive sampling, with a total sample of 65 people who really know or have competence with the topic of this research. The results of the GSCA analysis test show that: Transformational Leadership Style has a significant effect on employee performance, because testing models with moderation using the GSCA test shows that the results are significant with a critical value ratio of 6.78 and an estimated value of 0.699. The inhibiting factors in improving employee performance are, low employee performance, lack of employee discipline, mastery of the field work that is incompatible with the basic tasks and functions, slow administrative services in serving the community, leaders are less assertive towards subordinates, leaders lack creative thinking, do not have innovative and less open to new ideas. Transformational leadership style contributes to employees by 48.9% and the remaining 52.1% is influenced by other variables outside of this research variable. Keywords: transformational leadership style; employee performance